Residual Neuromuscular Block in the Elderly Patients: Incidence and Clinical Implications. Issue 3 (June 2016) - Murphy, Glenn S.; Szokol, Joseph W.; Avram, Michael J.; Greenberg, Steven B.; Shear, Torin D.; Vender, Jeffery S.; Parikh, Kruti N.; Patel, Shivani S.; Patel, Aashka
Abstract : (Abstracted from Anesthesiology, 123:1322–1336, 2015) Aminosteroid neuromuscular-blocking agents (NMBAs) undergo a substantial degree of organ-dependent elimination. Patients with age-related decline in organ function, such as elderly patients, may thus experience prolonged recovery and reversal times for NMBAs, which in turn may increase their risks for postoperative residual neuromuscular block (PRNB).